2010
DOI: 10.1093/protein/gzq021
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bacillus circulans β-amylase activity attained using the ancestral mutation method

Abstract: Thermostabilization of enzymes is one of the greatest challenges of protein engineering. The ancestral mutation method, which introduces ancestral residues into a target enzyme, has previously been developed and used to improve the thermostabilities of thermophilic enzymes. Herein, we report a study that used the ancestral mutation method to improve the thermostability of Bacillus circulans beta-amylase, a mesophilic enzyme. A bacterial, common-ancestral beta-amylase sequence was inferred using a phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…resurrection of an entire protein is not feasible, the insertion of ancestral residues in modern proteins can increase stability and enhance adaptability and tolerance to mutations (30). In addition, we have found that ancestral proteins tend to be more promiscuous to synthetic ligands or drug activation, especially in cases in which the ancestral proteins display a more promiscuous phenotype than the extant proteins for endogenous ligands.…”
Section: Discussionmentioning
confidence: 92%
“…resurrection of an entire protein is not feasible, the insertion of ancestral residues in modern proteins can increase stability and enhance adaptability and tolerance to mutations (30). In addition, we have found that ancestral proteins tend to be more promiscuous to synthetic ligands or drug activation, especially in cases in which the ancestral proteins display a more promiscuous phenotype than the extant proteins for endogenous ligands.…”
Section: Discussionmentioning
confidence: 92%
“…Noteworthy, large alignments of 238-2813 proteins were used in this study to predict the consensus. After screening of 662 colonies the authors were able to identify variants with 8°C increase in T 50 60 . Finally, in a similar study random mutagenesis was complemented with a consensus approach to improve thermostability of Clostridium thermocellum endoglucanase [39].…”
Section: Stochastic Approachesmentioning
confidence: 99%
“…Out of eight single and double variants produced, six showed up to 4.7°C increase in half-denaturation temperature. In a similar study thermostability of Bacillus circulans β-amylase was improved [50]. 20 ancestral mutations were selected based on 22 protein sequences.…”
Section: Stochastic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In others, point mutations were used to identify the residues that increased stability. They were then combined to increase the thermostability of the protein (Maxwell & Davidson, 1998;Nikolova et al, 1998;Yamashiro et al, 2010).…”
Section: Consensus Sequencementioning
confidence: 99%